Optimization of electric networks modes under conditions of partial uncertainty of initial information - Reymov Kamal; Makhmuthonov S. K.; Turmanova Gulnaz; Uzaqbaev Quwat (E3S Web of Conferences, 2021)
One of the problems of modern power systems management regimes associated with the probabilistic nature of the starting information. In such circumstances, the decision of relevant control tasks based on deterministic methods lead to unacceptable or non-optimal results. Therefore, this article questions optimization of energy systems based on functional limitations in terms of probability of the initial information